Methodological lessons in neurophenomenology: Review of a baseline study and recommendations for research approaches - Bockelman, Patricia; Reinerman-Jones, Lauren; Gallagher, Shaun (Frontiers in Human Neuroscience, 2013)
Neurophenomenological methods integrate objective and subjective data in ways that retain the statistical power of established disciplines (like cognitive science) while embracing the value of first-person reports of experience. The present paper positions neurophenomenology as an approach that pulls from traditions of cognitive science but includes techniques that are challenging for cognitive science in some ways. A baseline study is reviewed for “lessons learned”, that is, the potential methodological improvements that will support advancements in understanding consciousness and cognition using neurophenomenology. These improvements, we suggest, include (1) addressing issues of interdisciplinarity by purposefully and systematically creating and maintaining shared mental models among research team members; (2) making sure that neurophenomenological experiments include high standards of experimental design and execution to achieve variable control, reliability, generalizability, and replication of results; and (3) conceiving of phenomenological interview techniques as placing the impetus on the interviewer in interaction with the experimental subject.